THE EFFECTS OF CHITOSAN GEL IN WHITE RAT TOTAL LEUKOCYTES ON INCISION WOUND HEALINGS - Syafruddin, Syafruddin; Putri, Dessy Ayu Mega; Panjaitan, Budianto; Sayuti, Arman (Buletin Veteriner Udayana, 2022)
This study aims to determine the effect of chitosan gel on the number of white mouse leukocytes ( Rattus norvegicus ) on incision wound healing. This study used 10 female white rats that were 2 months old and weighed ± 165 g, that was designed with a Split-plot design using 10 rats and was divided into 2 treatment groups with each treatment group consisting of 5 replications. Treatment I (control) incision wound smeared with gentamicin ointment, treatment II incision wound smeared with chitosan gel 2 times a day for 14 consecutive days. This study used chitosan gel with a 5% concentration. Blood sampling through the lateral tail vein as much as 0.5 ml and observation of the number of leukocytes was carried out on days 0, 3, 7 and 14 after treatment. Examination of the number of leukocytes is done with a hemocytometer and using the Neubauer method. The parameters of this study are the number of leukocytes in the incision wounds healing process in white rats. The research data were analyzed using analysis of variance based on the Split-plot Design with the SPSS program. The number of leukocytes in group I (gentamicin) vs group II (chitosan) on days 0; 3; 7; and 14 was 7.89×104/mm 3 vs 7.30×104/mm 3 ;  6.28×104/mm 3 vs 10.23×104/mm 3 ; 7.27×104/mm 3 vs  10.28×104/mm 3 ; and 7.02×104/mm 3 vs 7.52×104/mm 3 , respectively. From the results of this study it can be concluded that the use of chitosan gel is better than gentamicin ointment in the healing process of incision wounds in white rats. The results of thisstudy can be followed by conducting research on other animals for wound treatment applications.